A social prospect theory of intergroup relations explains the occurrence of incremental progressive social change - Cropley, Ian; Jost, John T. (Frontiers in Social Psychology, 2024)
Throughout modernity, incremental progress has been a common pattern of social change. We propose a novel social prospect theory of intergroup relations that can explain the prevalence of this pattern by distinguishing between two types of social change: progressive and regressive. Progressive social change is defined as that which results in a new social system or regime, whereas regressive social change is that which results in a return to an earlier social system or regime. According to our proposed theory, which is an extension of prospect theory, (a) progressive social change represents possible gains for members of disadvantaged groups and potential losses for members of advantaged groups, whereas regressive social change represents possible gains for members of advantaged groups and potential losses for members of disadvantaged groups; (b) loss avoidance is a stronger motivator than gain-seeking; and (c) the likely outcomes of reverting to a previous state of affairs can be predicted with more certainty than outcomes of establishing a new and untested social system. When these three principles are applied to the context of group decision-making by members of advantaged and disadvantaged groups, a motivational tendency toward incremental progressive social change results. This is because members of advantaged and disadvantaged groups alike will be strongly motivated to avoid losing ground, but members of disadvantaged groups will be more strongly motivated than members of advantaged groups, because there is more certainty associated with the outcomes of regressive vs. progressive social change. Thus, social prospect theory provides a motivational explanation for the occurrence of gradual, incremental progressive changes despite the many sociopolitical disadvantages faced by beneficiaries.